At the intersection of court proceedings and arbitration in Europe: the exclusion of arbitration in the Brussels Ia Regulation - Klebes, Stephan Dominikus (Department of Commercial Law, 2017)
The exclusion of arbitration from the scope of application of the Brussels Regime on jurisdiction and the recognition and enforcement of judgments in civil and commercial matters in the EU has a long history and is still subject to controversy. After some introductory explanations of the legal framework and relevant principles in the field of law, this minor dissertation examines chronologically all possible involvements of national courts in arbitral proceedings in order to give an overview of the (in-) applicability of the Brussels Ia Regulation to them. For this purpose, the relevant case law of the CJEU and the related legal developments beginning with the adoption of the Brussels Convention up to the entry into force of the Brussels Ia Regulation are being considered. Finally, the legal problems arising from the current state of affairs and how courts should navigate it are discussed with an emphasis on the possible enforcement constellations of contradicting judgments and awards.